The Effect of Using Virtual Laboratories on Dynamic Electricity Topic on Student Learning Outcomes - Wiweka, Kiati; Ntobuo, Nova Elysia; Nurhayati, Nurhayati; Mursalin; Paramata, Dewi Diana; Uloli, Ritin (Journal of Classroom Action Research, 2025)
This research aims to determine the effect of student learning outcomes for those who use the dynamic electric virtual e-laboratory on student learning outcomes for those who use PPT at SMP Negeri 1 Wonosari. This type of research is quantitative research with experimental research methods. This research was carried out at SMP Negeri 1 Wonosari, which is located at Jatimulya Village, Wonosari District, Boalemo Regency, in the odd semester of the 2024/2025 academic year. This research design is a quasi-experimental design with a pretest-posttest control group design. The research results show that there is an influence on student learning outcomes. This is based on the hypothesis testing criteria, where t-count 2.09 is greater than t-table 2.02, and it can be concluded that hypothesis testing is t-count greater than t-table